Impact of Phet-Based Vs. Paper-Based Trigonometric Worksheets on Students’ Adaptive Thinking Skills - Usep Sholahudin; Rina Oktaviyanthi (International Journal of Pedagogy and Teacher Education, 2025)
Trigonometry learning often presents challenges as students struggle to apply mathematical concepts in real-world contexts. Traditional instruction tends to emphasize procedural fluency over conceptual understanding, limiting the development of students’ adaptive thinking skills. Digital tools like PhET simulations offer interactive visualizations that support conceptual learning, but their role in enhancing adaptive thinking remains underexplored. This study investigates the comparative effectiveness of PhET-based worksheets versus traditional paper-based worksheets in fostering adaptive thinking in trigonometry. The study involved 80 first-year students from Universitas Serang Raya’s Mathematics Education and Informatics Engineering programs, enrolled in the 2023–2024 Calculus course. Participants were divided into an experimental group using PhET-based worksheets and a control group using paper-based worksheets. Data were collected through pre-tests, post-tests, and student preference questionnaires, and analyzed using independent t-tests. Results show that the PhET group outperformed the control group, with a 35% improvement in adaptive thinking skills versus 20% in the control group (p < 0.05). Students using PhET-based worksheets demonstrated greater flexibility in applying trigonometric concepts, creative problem-solving, and knowledge transfer to real-life situations. In contrast, the paper-based group showed moderate gains, particularly in structured and procedural problem-solving. Questionnaire responses revealed that students appreciated the interactivity and engagement of PhET-based media, while also valuing the focus and clarity offered by paper-based worksheets. These findings highlight the potential of a blended learning approach that combines digital interactivity with structured offline tasks to enhance adaptive thinking. Future research should explore the long-term effects and broader applications of such strategies in mathematics education.